Chachaklum, a viable initiative? - Lundström, Ella (2014)
Due to poorly functioning local and regional markets, the smallholders in San Francisco, Petén, were dependent on intermediaries that took advantage of the smallholder’s distance to markets. In an attempt to secure income and strengthen their bargaining position, 189 smallholders joined forces through the creation of a social smallholder network, held together by a community based enterprise. This enterprise was initiated in 2011 with the help of government incentive programmes and NGOs that within a few years will leave the enterprise to auto regime.